PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KUALITAS PELAYANAN PADA PUSAT PEMBERDAYAAN PEMUDA DAN OLAHRAGA NASIONAL (PP-PON) KEMENTERIAN PEMUDA DAN OLAHRAGA TAHUN 2015 - Oni Trianto (KENEGARAAN, 2016)
The aims of research is to analyse influences of discipline and motivation to service quality in Pusat Pemberdayaan Pemuda dan Olahraga Nasional (PP-PON). The research describes service quality is positive influenced but insisgnificant, on the other hand, motivation has positive and significant influenced. furthermore, if coefficient of discipline has 1 value so it increases service quality around 0,063. Moreover, if coefficient of motivation has 1 value so it increases service quality around 0,779. Both motivation and discipline have 35,1% percent, meanwhile, 64,9% is influenced by others variables that is not including in regression model.Keywords: Discipline, Motivation, Service Quality